Impacto da comunicação de más notícias na formação do estudante de medicina: um relato de experiência - Bussi, Giovanna (Universidade Federal de São Carlos, 2024)
Communicating bad news is a necessary skill for a health professional who seeks integrated and humanized care, and is therefore part of the training of medical students. However, in addition to being a skill, it is also an event, which can bring different experiences and impacts to these future developing professionals.The aim of the work is to explore this experience, discussing its positive and negative aspects, as well as the need for its valorization and debate in an academic environment, aiming both at complete training and benefit in the patient care process, in addition to ways of personal and professional learning on the part of students. This is an experience report, complemented with a bibliographical survey to explore the topic in national and international databases. It is concluded that the reflection on the topic and recognition of its importance reveal the need to implement feasible and applicable strategies for teaching communication skills in medical training.
Impact of communication of bad news upon medical student formation: an experience report
Keywords: Communication; Comunicação; Más notícias; Communication strategy; Medical training; Doctor-patient relationship; Bad news; Relação médico-paciente; Estratégias de comunicação; Formação médica; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA